Improvement of Public Health Through Waste Bank Schematic Design - Arief Funna; Machfuzah Machfuzah; Sofyan Sofyan3; Deassy Siska; Savira Ersa (Faculty of Medicine University of Malikussaleh, 2022)
Abstract: The community health public in Indonesia needs to be improved to elevate the quality of life. The waste bank is an activity of a non-governmental program to maintain environmental health by separating the household waste into organic and non-organic categories. The waste bank is managed using a system such as banking conducted by officers. It was proven that waste bank activity has a positive impact on declining waste volume to improve sanitation. However, waste banks are still carried out in volunteering houses, public service houses, and residential paths. Waste banks have many potencies to support either ecotourism or eco-green planning. This study was performed by waste generation and characterization sampling to determine the required size of the waste bank schematic design. The result shows a schematic design model of the Waste Bank building by researching society’s needs for better environmental health. Purpose: This research is to design a waste bank based on public health needs Patients and methods: This study is a descriptive study with a cross-sectional approach. The sampling technique used is stratified random sampling, with 98 respondents residing in Lhokseumawe city. Data collection was done by 8 days of sampling. Results: The results showed that there is no waste bank building that meets the public health building requirements. There is a schematic design to propose. Conclusion: There is an urgency to have a requirement to waste bank building design to improve sanitation and public health.